Improving Access to Public Transportation for Canalside Communities near Kasetsart University, Bangkhen - Kaewko Leopairojna, Supaporn (Journal of Architectural/Planning Research and Studies (JARS), 2018)
Canals in the areas around Kasetsart University were once important transportation routes. Since then, however, people’s lifestyles have changed. Roads and sois are now the main means of transport. Meanwhile the areas along the canals are neglected, even though they can accommodate other modes of travelling such as walking and cycling. The researchers surveyed the physical environment and transportation network in the study area, gauged local resident opinions about travelling, and recommended how to improve access to public transportation using areas along the canals and routes selected by respondents. The respondents were 103 representatives of households living in communities in areas along the canals. The study showed that the respondents would travel more often by foot and bicycle if walkways or bikeways, which connect residents with public transportation systems, were improved. Enhancing the quality of these routes, according to the physical environment and the preferences of local residents, would provide more transportation modes and feed passengers into the public transportation systems. This in turn would help alleviate problems from traffic congestions effectively and sustainably. Moreover, the increasing role of canals in transportation will make people appreciate their importance and so take greater care to preserve the cleanliness of the water, thereby making the surrounding areas nicer places to live in.